ANALYSIS OF LIFE FORMS OF SCUTELLARIA SPECIES DISTRIBUTED IN THE FLORA OF FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
The article presents information on the analysis and classification of life forms of skullcap species common in the flora of the Fergana Valley, based on the classifications of S. Raunkier, I.G.Serebryakov.